Pengaruh Strategi Pembelajaran dan Pengetahuan Awal Terhadap Hasil Belajar Teknik Listrik Dasar Otomotif Siswa SMKN 1 Kota Bekasi - Siti Muawanah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2017)
The purpose of this research is to obtain empirical data about the effect of Instructional strategies and prior knowledge on the outcomes of basic electrical automotive of class X-class of SMK Light Vehicle Engineering. The method used in this research is the experimental method with the design of treatment research by level 2 x 2. Based on the results of hypothesis testing and discussion of research, the results obtained research as follows: First, the results of Electrical Engineering Basic Elementary studies in groups that use learning strategy project base learning higher than the group using expository learning strategies in class X students. Secondly, there is an interaction effect between learning strategy and prior knowledge on the outcomes of basic electrical automotive class X students. Third, the group of students with high prior knowledge, basic automotive is higher if using the learning strategy project base learning compared with using expository learning strategy. Fourth, in the low prior knowledge group, there was not difference between using project base learning strategy and using the expository learning strategy.